Tertiary Student Intention in Agricultural Sector Using Technology in Order to Maintain Food Security in West Java - Ulfah, Halida; Furoidah, Ayu; Zuhair Aulia, Teuku Muhammad Zahid; Sulyani, Agnesia Candra; Larasati, Niken (The Asian Journal of Technology Management (AJTM), 2023)
Abstract. Food security is urgently needed in 2050. Facing current conditions, the agricultural industry in Indonesia no longer appeals to the younger generation, and many farmers are elderly; the challenge of limited land, human resources, and falling farmer regeneration is a global one. This study investigates the desire of tertiary students in West Java, Indonesia, to pursue a profession in agriculture. The study's goal is to identify the elements influencing tertiary students' intentions to contribute or pursue a profession in agriculture, the correlation between those factors, and the things that may boost tertiary students' desire in continuing their career in agriculture. The study will look at the effects of a student's income, land availability and ownership, the student's parents' background in a specific demographic, and the influence of contemporary agricultural technology and data. Using quantitative research design and ordinal logistic regression analysis method, the study found that the father's education, willingness lives in the village, and the data-driven agriculture variable influenced tertiary students' interest in the agricultural industry.  Keywords:  Agricultural sector, food security, intention, technology usage, tertiary students.